Students’ Intention Towards Entrepreneurship: A Study On Engineering Students In Central Chhattisgarh (Journal of Namibian Studies : History Politics Culture, 2023)
Entrepreneurship has been being encouraged more emphatically for a decade amongst youth in the country. Various schemes like Swarojgar Yojna, Kaushal Vikas Yojna, Anganbadi etc. are running in urban and rural areas. The study is an attempt to measure the intention of entrepreneurship among the engineering students and also to identify the determinants of such intention. The study has been planned through causal model based on primary data collected from the engineering students of central Chhattisgarh. The study is expected to contribute to the entrepreneurship model for students as well as to the further studies.